IDENTIFYING ELEMENTS OF INTERCULTURALISM AND LANGUAGE MEDIATION IN THE “MODERN GREEK PAIDEIA” PROGRAM - Pichas, Alexandros (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2024)
This study delves into the intricate tapestry of interculturalism and language mediation within the textbooks of the 8th grade of the program “Modern Greek Paideia”, which is being used for the teaching of Greek as heritage language in “Aristotle” school, the only primary school in Toronto that the Hellenic Republic recognizes. More precisely, using discourse analysis as a method, the reconstitution of the whole cultural relationship between the dominant culture and the target culture is done through the cultural elements that exist in the textbook’s activities and images. This aims to show that foreign-language teaching textbooks play an important role in configuring multicultural societies with intercultural competence and acquiring a second language in diasporic environments. The present study is structured into the following two parts. First, a literature review of second/foreign language acquisition theories, intercultural education and teaching Greek as diasporas was conducted. Second, the textbook was analysed before the results were presented, and a discussion about teaching Greek as a heritage language was held. This research contributes to the burgeoning discourse on intercultural education and language pedagogy by offering empirical evidence and practical insights into fostering intercultural competence and linguistic mediation skills among young learners. Ultimately, the findings aim to inform curriculum design and pedagogical approaches that promote inclusive and culturally responsive education within the “Modern Greek Paideia” program and beyond.